An Analysis Students’ Motivation in Reading ProcedureText at the First Grade of SMA N Rambah Samo - Kasyulita, Evi; Sari, Desi Ratna (J-SHMIC : Journal of English for Academic, 2016)
This research discussed  about  students motivation in reading procedure text at the first grade of SMAN I Rambah Samo.  This research is important  to conducted  because with  analysis students motivasion can  preapared steps to increasing students reading  skill.t The technique of analyzing the data the researcher was  descriptive qualitative. Questionnaire was used to collect the data. The finding showed that there was any significant  analysis  students’ motivation. It could be  showed that from 21 students in reading procedure text, there were10 students (60-79%) in  good, 4 students  (50-59%) and in  poor,and 7 students (0-49) very poor category.